The Pathophysiology of Heart Failure in Children: The Basics - Knudson, Jarrod D. (Curr Cardiol Rev, 2016)
Few data exist on the pathophysiologic changes in pediatric heart failure. Most of the knowledge has evolved from animal models of ischemic or idiopathic dilated cardiomyopathy. This review addresses the pathophysiologic changes that occur in the failing heart from animal models and the adult experience to unique aspects of heart failure in children.